Kesuksesan Wirausaha di Era Digital dari Perspektif Orientasi Kewirausahaan (Study Literature) - Zulkifli; Sugiarto, Irwan; Napu, Fithriah; Rukmana, Arief Yanto; Hastuti, Puji (Sanskara Ekonomi dan Kewirausahaan, 2023)
This study aims to evaluate the relationship between entrepreneurial orientation and entrepreneurial success in the digital era based on literature studies. Entrepreneurial orientation is seen as a key factor that can help entrepreneurs to face challenges and take advantage of opportunities that arise in the digital era. The literature study method is used to collect and evaluate literature related to entrepreneurial orientation and entrepreneurial success in the digital era. The results of this study indicate that a good entrepreneurial orientation can help entrepreneurs develop their skills in utilizing digital technology and adapting to changes in the digital era. This literature study concludes that entrepreneurial orientation is an important factor that needs attention in achieving entrepreneurial success in the digital era.